Lettere e Rime Introduzione e commento - Matraini, Chiara (Premio Ricerca «Città di Firenze», 2018)
The commentary of Lettere e rime which Chiara Matraini (1515-1604) published in Venice with the editor Moretti in 1597, when she was 82, intends to provide an organic analysis of the composition, of the relationship between the genres, of the modalities of the "imitatio" and of the philosophical, social and cultural substrate acting as a background in her last chansonnier. The study also focuses on her stylistic changes over a period of forty years (1555-1597), from the adherence to Petrarch and Bembo's canon to the end-of-the-century Mannerism, as well as on the counter-reformist twist characterizing a parallel writing of philosophical and devotional nature, which can be seen here between the lines. The investigation also takes the liber of Lettere e rime as a deliberately organic and structured whole in the meeting between the letters and the poems. By virtue of its 'marginality' as well, this shows a complex work, emerging together with the many afterthoughts which animated the long, almost century-long, life of the author from Lucca.